Effectiveness of Smoke-Free Campus Implementation on Smoking Behavior Control - Trirasetya, Mutiara Ulfa; Leonardi, Felix; Suhartomi, Suhartomi; Sihotang, Widya Yanti; Edison, Rizki Edmi (Poltekkes Kemenkes Tanjung Karang, 2024)
The tobacco industry is a significant obstacle in the effort to control smoking behavior, especially since they are allowed to promote their products to the public, including students. To address this issue, the Ministry of Health developed a smoke-free zone that may be implemented in universities to reduce smoking rates among adolescents. To know the effectiveness of implementing a smoke-free campus policy on smoking behavior control at Universitas Prima Indonesia by assessing aspects of student knowledge and compliance levels. This research is a descriptive quantitative study with a cross-sectional design and uses purposive sampling techniques with the criteria of active smoker students, 74 people in the medical study program of the Faculty of Medicine, Dentistry, and Health Sciences at Universitas Prima Indonesia. Data was obtained in February-April by distributing questionnaires directly to student smokers. The results showed that smoking behavior control among students increased in 50 (67.6%) out of 74 respondents. This is supported by the relationship between the level of knowledge and students' attitudes toward smoking behavior control in the smoke-free campus area, as indicated by a p-value<0.05 (0.005<0.05 and 0.001<0.05). This study found that students’ knowledge and attitudes towards smoke-free campus areas are important aspects influencing the effectiveness of the smoke-free campus policy in controlling smoking behavior.